1993
DOI: 10.1029/93wr00283
|View full text |Cite
|
Sign up to set email alerts
|

Compositional simulation of groundwater contamination by organic compounds: 1. Model development and verification

Abstract: A compositional simulator is developed for application to the analysis of contamination and remediation of groundwater systems. Simultaneous flow of three fluid phases (water, gas, and organic) is modeled. Interphase partitioning and transport of an arbitrary number of organic and inorganic components can be simulated. Phase densities are functions of pressure and phase composition. The model includes several numerical options, ranging from fully implicit with first-order upstream weighting to implicit in pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(54 citation statements)
references
References 36 publications
(20 reference statements)
0
52
0
2
Order By: Relevance
“…The work of Sleep and Sykes (1989) also used the IMPES, solving the Richards equation for the water phase and then explicitly calculating the behavior of the air phase. In a more recent work, Sleep and Sykes (1993) compared the accuracy and efficiency of both an IMPES scheme and a fully implicit scheme. They found that the IMPES was more restricted in time step size than the fully implicit scheme.…”
Section: -7 Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The work of Sleep and Sykes (1989) also used the IMPES, solving the Richards equation for the water phase and then explicitly calculating the behavior of the air phase. In a more recent work, Sleep and Sykes (1993) compared the accuracy and efficiency of both an IMPES scheme and a fully implicit scheme. They found that the IMPES was more restricted in time step size than the fully implicit scheme.…”
Section: -7 Discussionmentioning
confidence: 99%
“…The strong tradition of the use of this method dates back to early applications to petroleum reservoir problems. Among the numerous users of this method are: Pinder and Abriola (1986) who solved the fully coupled three phase problem using an implicit finite difference model with a Newton Raphson non-linear iteration scheme, with the assumption of a constant-pressure immobile gas phase, Pmess (1987) with the coupled heat and mass flow model TOUGH Sleep and Sykes (1989); Culver et al (1991); Moridis and Reddell (1991);and Sleep and Sykes (1993) whose model is one of the most complete currently available. The model of Sleep and Sykes (1993) solves the fully coupled air and water flow equations and includes contaminant transport in both phases.…”
Section: -7 Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Du fait de la complexité de la représentation du biofilm (modèles de Monod, des Micro-colonies et du Biofilm) et des interactions physico-chimiques, la majorité des problèmes traités sont unidimentionnels. Quelques modèles numériques bidimensionnels (RIFAI et al, 1988;ODENCRANTZ, 1992;MILLS et al, 1991) et tridimensionnels (SLEEP et SYKES, 1993;ZHENG, 1993) ont toutefois été développés. Optant pour une simplicité dans l'approche modélisatrice qui n'enlève rien à une exploitation efficiente des résultats, le problème étudié ici est unidimensionnel.…”
Section: Introductionunclassified